2006
DOI: 10.1037/0894-4105.20.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Understanding predictors of functional recovery and outcome 30 months following early childhood head injury.

Abstract: Much is known about outcome following traumatic brain injury (TBI) in school-age children; however, recovery in early childhood is less well understood. Some argue that such injuries should lead to good outcome, because of the plasticity of the developing brain. Other purport that the young brain is vulnerable, with injury likely to result in a substantial impairment (H. G. Taylor & J. Alden, 1997). The aim of this study was to examine outcomes following TBI during early childhood, to plot recovery over the 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
201
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(237 citation statements)
references
References 76 publications
33
201
2
1
Order By: Relevance
“…Pediatric traumatic brain injury (TBI) results in substantial neurobehavioral morbidity for survivors, including persistent impairments in emotional, social, behavioral, and neuropsychological functioning that persist well beyond the acute phase of injury (e.g., Anderson et al, 2001Anderson et al, , 2006Taylor et al, 2002;Yeates et al, 2005). A clear relationship has been observed for physical and cognitive outcomes in TBI, with the severity of TBI contributing to greater impairment .…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric traumatic brain injury (TBI) results in substantial neurobehavioral morbidity for survivors, including persistent impairments in emotional, social, behavioral, and neuropsychological functioning that persist well beyond the acute phase of injury (e.g., Anderson et al, 2001Anderson et al, , 2006Taylor et al, 2002;Yeates et al, 2005). A clear relationship has been observed for physical and cognitive outcomes in TBI, with the severity of TBI contributing to greater impairment .…”
Section: Introductionmentioning
confidence: 99%
“…Although research involving young children with TBI is scant, several researchers have demonstrated that children injured at a younger age have worse neurobehavioral outcomes than children injured when they are older (Anderson et al, 2005). Because many neurobehavioral skills are emerging rapidly during early childhood, young children may be particularly susceptible to long-term disruption of neurobehavioral development (Anderson et al, 2005(Anderson et al, , 2006. Because of high incidence, morbidity, and survival, TBI in early childhood is a serious health concern that affects a large number of children, families, and communities.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Few studies, however, have prospectively followed survivors of early TBI into adolescence, and those available focus primarily on cognition. In addition, several factors have been identified that contribute to deficits after school-aged TBI (injury severity and age, premorbid child and family function), [9][10][11][12][13] but it is unclear whether these factors also explain outcomes for younger children.…”
mentioning
confidence: 99%